The Effect of Resilience on Health with Social Support as a Moderator for Health Workers in Jakarta During the Covid-19 Pandemic - Saputra, Rendy; Roswiyani, Roswiyani (Bulletin of Science Education, 2024)
Healthcare workers are currently preoccupied with the COVID-19 pandemic, causing the risk of mental disorders. This study aims to determine the effect of resilience on health with social support as a moderator for healthcare workers in Jakarta during the COVID-19 pandemic. Participants in this research were healthcare workers, either doctors or nurses who were working in hospitals or health clinics in Jakarta during the COVID-19 pandemic. Research participants are at least 20 years old, male and female, and not limited by religious background, culture, social status, and length of time as a healthcare workers. Measurement of resilience variable using the RQ Test made by Reivich and Shatte, social support variable using the Multidimensional Scale of Perceived Social Support (MSPSS) made by Zimet et al, and health variable using the SF-36 measurement scale made by RAND Corporation. Based on the results of the regression analysis, this study has the result that resilience has a significant effect on the health condition of healthcare workers, which means that the more resilient a person is, the better the individual’s health will be. Resilience moderated by social support has a significant effect on health, which means that social support is able to strengthen the relationship between resilience and the health of healthcare workers in Jakarta during the COVID-19 pandemic. Keywords: Healthcare Workers, Resilience, Social Support